Nosocomial Clostridium difficile Diarrhea in Patient with Malignancy - Andree Kurniawan; Ari Fahrial Syam; Nata Pratama; Resti Mulya Sari; Khie Chen (The Indonesian Society for Digestive Endoscopy, 2011)
Clostridium difficile (C. difficile) is the main pathogen causing antibiotics associated diarrhea and colitis. This bacterium increases with hospitalization with incidence of 20-60 cases per 100,000 patients/day. C. difficile is gram positive bacilli which produce toxins in 2,700 cases in every 100,000 exposures to particular antibiotics, such as clindamycin, cephalosporin, and ampicillin. These antibiotics disrupt the intestinal normal flora and predispose to colonization of C. difficile. This case described a 53-year old male patient with squamous cell carcinoma in his left ear who came to Department of Internal Medicine, Cipto Mangunkusumo Hospital, with the complain of diarrhea since two weeks after one month hospitalization in Department of Ear, Nose, and Throat. The characteristics of the diarrhea were 10 times per day ± 100 mL, watery consistency, green yellowish in color, and no blood in the feces. Additionally, the patient also complained of pain in all parts of his stomach, especially in the epigastric area. Earlier, patient was given ceftazidime for 30 days of hospitalization. The serology examination of C. difficile in the feces showed positive result (titer = 0.790 and control = 0.190). During the colonoscopy examination, pancolitis was found and the pathologic anatomy result was found appropriate for infective colitis. Thereafter, antibiotic administration was ceased and metronidazole was administered intravenously three times a day. The diarrhea stopped after seven days and the patient was discharged. Keywords: Clostridium difficile, nosocomial diarrhea, malignancy